The small guide to anxiety - Small, Gary, 1951-; Vorgan, Gigi, 1958- (West Palm Beah, FL : Humanix Books, 2019)
Is anxiety hurting your performance at work, at school, or affecting your relationships? In "The Small Guide to Anxiety", Dr. Gary Small shows how to gain back your control: how to tell the difference-an anxiety disorder or normal worries; how to find a therapist that's right for you; how to overcome generalized anxiety disorder (GAD) in just weeks; how to stop a panic attack instantly, with a small item in your pocket or purse; a breakthrough therapy with a 90 percent success rate in getting rid of phobias; "neuromodulation" techniques that reduce your anxiety; ways [to] improve your sleep if you suffer from anxiety; and much, much more. "The Small Guide to Anxiety" will show you which therapies work best to help you overcome these anxieties, and lead a richer, fuller, more satisfying life. -- From publisher's description.
What is anxiety? -- Do-it-yourself strategies for reducing anxiety -- Conventional treatments that work -- Alternative therapies -- Worried sick : generalized anxiety disorder -- Gripped by fear : panic disorder -- Shy to a fault : social anxiety -- Germs, bugs, and heights, oh my : phobias -- Can't stop those thoughts : obsessive-compulsive disorder.
"Solutions for: panic attacks; phobias; obsessive thinking; compulsive behavior; insomnia; intense self-doubt; social anxiety; digestion issues; tech anxiety; medication abuse"--Cover.
Includes bibliographical references (pages 171-185) and index.
Keywords: Anxiety -- Treatment; Self-care, Health; SELF-HELP / Anxieties & Phobias; SELF-HELP / Compulsive Behavior / Compulsive Behavior / Obsessive Compulsive Disorder (OCD); SELF-HELP / Emotions; Anxiety -- Treatment; Self-care, Health; Self-help publications; Self-help publications